Evaluation of the Nutritional and Hematological Status of Sickle Cell Children Monitored in the Pediatric Department of the University Hospital Center of Yalgado Ouedraogo - Angèle, Kalmogho; Makoura, Barro; Constant, Paré Boyo; Ibrahima, Ouédraogo; Habibata, Bambara; Chantal, Zoungrana; Rolande, Kaboré; Flore, Ouédraogo; Oumarou, Sawadogo; Caroline, Yonaba; Desiré, Dahourou Lucien; Fla, Kouéta (International Journal of Child Health and Nutrition, 2020)
Objective: To assess the nutritional and hematological status of sickle cell children followed in the department of pediatrics of the Yalgado Ouédraogo University Hospital Centre (CHU-YO). Methodology: This was a cross-sectional study conducted from September 1, 2017, to February 28, 2018. All children with major sickle cell syndrome followed in the department of pediatrics at the CHU-YO and following their follow-up appointments were included in the study. Results: We included 230 children aged 11 months to 16 years with an average age of 8.5 years. The sex M/F ratio was 1.09. The SC heterozygotes were the most represented with 56.52%. The average hemoglobin level was 9.39 g/dl. The prevalences of wasting, stunting and underweight were respectively 23.04%, 15.65%, and 13.89%. In univariate analysis, the factors associated with emaciation was hyperleukocytosis (p=0.002).The factors associated with stunting were leukocytosis (p=0.01), severe anemia (p=0.01), SS phenotype (p=0.002), age range of 5-10 years (p=0.007), Secondary (P=0.007) and higher level (p=0.001) of father’s education, secondary (p=0.027) and higher level (p=0.034)of mothers’education , farmer(p=0.003) trader (p=0.042), and informal occupation of father (p = 0.002),and breastfeeding duration after 24 months (p=0.006). For underweight associated factors in univariate analysis were SS phenotype (p=0.003) and severe anemia (p=0.01). Conclusion: The prevalence of different types of malnutrition deficiency of sickle cell children followed at CHU-YO was high. It is important to strengthen the nutritional monitoring of children with sickle cell disease for better management of the disease.